Laser surface processing of magnesium alloys - Khadka, Indira (2019)
Magnesium and its alloys are promising biomaterials for temporary implants. They have superior properties compared to other metallic biomaterials such as high specific strength, biodegradability and physiological compatibility. However, Mg has the inconvenience of rapid degradation at the initial stage prior to the formation of magnesium oxide under an environment of pH ranging from 7.4 to 7.6, which may cause its failure. For Mg and its alloys to be used as a biomaterial, surface properties and morphology should be modified properly to achieve a slow degradation rate as well as biocompatibility. Laser surface engineering is a promising approach for the surface modification of different materials. The rapidly heating and cooling process during laser-material interactions results in a change in the surface properties with or without changing the properties of the bulk material. As such, laser surface treatment is investigated for the modification of the surface properties of rare earth-Mg alloys to improve the degradation resistance and wettability properties. In particular, the research focuses on the surface modification of WE54 Mg alloy for bio-applications. This alloy is commonly used for aerospace and automobile industry. However, its potential usage for bio-application has not been explored. Different types of lasers, namely femtosecond, picosecond, and Nd: YAG lasers were employed to gain an understanding of the ultrafast laser-material interaction with WE54 Mg alloy. In particular, the resulting laser irradiated surface structure of WE54 was analyzed. A random microstructure was observed when the surface was irradiated by the femtosecond laser with a pulse energy of 84 μJ. The surface consisted of buds like microstructure, which appeared grey and slightly yellowish. Selective vaporization and change in optical properties of the surface was observed. A periodic surface structure was observed when the surface was irradiated by the picosecond laser with a pulse energy of 50.2 µJ. This periodic structure can act as a diffraction grating. The initial single scanning observation suggested a change in optical properties of WE54 alloy. Formation of clusters and particles distribution was higher in picosecond laser than that of femtosecond laser. More particles were deposited on the surface during the picosecond laser irradiation process. Using the Nd: YAG laser, surface irradiation of WE54 was studied at different laser power parameters. Granular, cellular and ripple surface structures were observed with the laser power density of 1.307 × 105, 2.770 × 105, and 3.901 × 105 W/cm2, respectively. Less protruded particles were observed at high laser power density. High power Nd: YAG laser irradiation resulted in the formation of variable surface structures including granular, coarse, flower as well as ripple structures. The optimized Nd: YAG laser parameters of frequency 10 kHz, 20 mm/s scanning speed, 50% overlapping and 0.001 mm hatching density were used for further treatment and characterization of WE54 alloy. For the degradation behavior in simulated body fluid of WE54 alloy, the surface was irradiated with a laser power density of 2.770 × 105 W/ cm2 (at laser power of 100 W and focal length 152.5 mm). Dissolution of the α-Mg matrix, as well as melting of second phase particles and their redistribution on the surface, was observed on the laser irradiated surface. The concentration of the Y element was increased from 5% to 12.15 %. The corrosion potential was reduced to less negative values from -1.810 V to -1.503 V. The two weeks immersion test in SBF resulted in weight loss improvement by 30%, namely from 11.43 mg without laser treatment to 7.952 mg after laser treatment. In addition, Nd: YAG laser treatment had a significant effect on the wetting behavior of the WE54 alloy due to the changes of surface microstructure, surface roughness and oxygen content. With the laser power density ranging from 1.307 to 3.901 × 105 W/cm2, the concentration of rare earth elements Y and Nd along the grain boundaries was increased and the overall concentration of Mg was reduced. The changes in the surface structure and chemical elements of WE54 alloy reduced the contact angle from 60.84o before laser treatment to 23.13o after laser treatment. The reduction of contact angle is an indication of better wettability of WE54 after laser irradiation. Furthermore, to study cell viability on the WE54 alloy, surface irradiation with Nd: YAG laser power density of 3.901×105 W/cm2 was carried out with SBF solution covering the WE54 surface. During the laser irradiation process, deposition of calcium and phosphate elements, originating from the SBF solution, was obtained on the WE54 surface. The deposited Ca/P layer on the surface of WE54 alloy can act as hydroxyapatite layer for the cells activity. The cells propagation rates on the laser modified surface with SBF solution were faster than for the untreated surface which was verified by the PrestoBlue test for cell viability. The reduction of PrestoBlue reagent changed from 46.83 % in as-received WE54 to 61.34 % in the laser treated surface with SBF. This indicates that the activity of the cells was high for the laser modified surface of WE54 in the presence of SBF solution. In summary, the interaction of WE54 with different lasers was explored. The Nd: YAG laser was chosen to study the degradation, wettability and cell viability characteristics of WE54 alloy. The laser modified surface of WE54 alloy showed improvement in surface properties by controlling its degradation properties. The laser treatment method with the SBF solution generated a surface with Ca and P ions on WE54 surface and this surface resulted in an improvement in the cells activity.